Integrated Critical Care Curriculum for the Third-Year Internal Medicine Clerkship - Daniel Gergen; Joshua Raines; Bryan Lublin; Anna Neumeier; Bill Quach; Christopher King (Association of American Medical Colleges, 2020)
Introduction A majority of residents provide care for critically ill patients, yet only a minority of medical schools require ICU rotations. Therefore, many medical students enter residency without prior ICU experience. The third-year internal medicine (IM) clerkship at our institution's Veterans Affairs Medical Center (VAMC) provided an opportunity for medical students to rotate through an open ICU as part of their inpatient ward rotation. Prior to March 2019, no structured critical care curriculum existed within the IM clerkship to prepare students for this experience. Methods We created a seven-session ICU curriculum integrated within the VAMC IM clerkship addressing core critical care topics and skills including bedside presentations, shock, and respiratory failure. IM residents facilitated the curriculum's case-based, small-group discussions. We assessed curricular efficacy and impact with a pre- and posttest and end-of-curriculum survey. Results Forty-one students participated in the curriculum from March to November 2019. As a result, students agreed that their overall clerkship experience improved (73% strongly agree, 24% agree). Students also reported increased comfort in their ability to participate in the management of critically ill patients (44% strongly agree, 51% agree). Objectively, student performance on a 15-question pre- and posttest improved from a precurricular average of 7.5 (50%) questions correct to a postcurricular average of 10.7 (71%) questions correct (p <.0001; CI 2.2-4.4). Discussion Following implementation of our ICU curriculum, medical student attitudes regarding overall IM clerkship experience, self-perceived confidence in critically ill patient management, and medical knowledge all improved.